Review of Modern Writers, Transnational Literatures: Rabindranath Tagore and W. B. Yeats, by Ragini Mohite - Mina M. Đurić (Review of Irish Studies in Europe, 2022)
Review of Modern Writers, Transnational Literatures: Rabindranath Tagore and W. B. Yeats, by Ragini Mohite (Clemson, SC: Clemson University Press) 2021, ISBN: 978-1-949-97906-0, 256 pp., $120 (hardback)